Analytical and experimental characterization of viscous fan clutch performances including thermal dynamics. (March 2017) - Yin, Zhihong; Zhao, Kegang; Shangguan, Wenbin; Song, Liming
This paper presents an investigation on the performance characterization of viscous fan clutch with double grooves including thermal behaviors. A detailed mathematical model of the fan clutch is established by taking into account the viscosity variation of the viscous fluid with shear radius and temperature, and an iterative algorithm is proposed to calculate the performances of the fan clutch. Laboratory experiments are then carried out on a performance measurement setup for viscous clutch, for validating the proposed mathematical model and calculation method. Based on the verified model and calculation algorithm and the experimental setup, the performances of six alternative viscous fan clutch designs are studied. The combined analytical/experimental results suggest that the clutch performances degrade with the increase of the input speed, and the proposed model and calculate method are valid and can be successfully employed to facilitate the design of new viscous fan clutches as well as control system development, for saving cost and shortening development period.